2019
DOI: 10.1097/ajp.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Psychological, Social, Physical Activity, and Sleep Measures and Somatosensory Function in Individuals With Spinal Pain

Abstract: Objective: Somatosensory abnormalities are linked to clinical pain outcomes in individuals with spinal pain. However, a range of factors might confound the relationship between altered somatosensory function and clinical pain outcomes. This systematic review aimed to evaluate the literature to assess the level of evidence of associations between psychological, social, physical activity, and sleep measures and somatosensory function (assessed via sensory psychophysical testing) among individuals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 104 publications
2
14
0
1
Order By: Relevance
“…Studies on the relationship between QST and psychosocial variables have largely yielded low associations in heterogeneous populations, with catastrophizing showing some of the strongest correlations 30 . Catastrophizing and anxiety have each been shown to be associated with heat pain threshold in adults with chronic pain 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the relationship between QST and psychosocial variables have largely yielded low associations in heterogeneous populations, with catastrophizing showing some of the strongest correlations 30 . Catastrophizing and anxiety have each been shown to be associated with heat pain threshold in adults with chronic pain 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with LBP who display a nociceptive mechanism may present with QST profiles more similar to normal controls, whereas subjects with a CS mechanism may display many of the aforementioned QST characteristics associated with CS. Also, it is worth noting that psychological variables such as anxiety and depression have a small, negative association with pain thresholds, so these should be accounted for when predicting outcomes using QST measures in patients with spinal pain 30 …”
Section: Introductionmentioning
confidence: 99%
“…71 The absence of predictive ability of QST findings in some studies can be explained by the moderating effects of psychosocial and lifestyle factors, such as sleep and physical activity. 72 A systematic review and metaanalysis in April 2018 that included 37 studies and 3860 participants with musculoskeletal diseases concluded that baseline QST measures of central sensitisation predicted major outcomes such as pain (mean r 0•31, 95% CI 0•23-0•38; n=1057) and disability (mean r 0•30, 95% CI 0•19-0•40; n=290). 73 Baseline temporal summation (mean r 0•37, 95% CI 0•17-0•54) and conditioned pain modulation (mean r 0•36, 95% CI 0•20-0•50) were also associated with pain at followup.…”
Section: Central Sensitisation and Prognosismentioning
confidence: 99%
“…In particular, psychological factors such as mental health problems (e.g., depression, anxiety) are associated with poor sleep (Finan et al, 2013;Vincent et al, 2015). Catastrophizing, as well, has been associated with reduced sleep quality (Othman et al, 2019). Reviews of the biopsychosocial model of pain have generally highlighted interrelationships between sleep and psychological factors such as distress, and some reviews have suggested that sleep disruption is a critical pathway by which negative affective processes affect long-term pain outcomes (Buenaver et al, 2012;Edwards et al, 2006Edwards et al, , 2011Finan et al, 2013).…”
Section: Sleepmentioning
confidence: 99%